THE ROLE OF AL-URF IN CONTEMPORARY ISLAMIC ECONOMIC LEGAL ISSUES: SUSTAINABLE BUSINESS PRODUCTION DEVELOPMENT - Santika, Ana; Ghozali, M. Lathoif (Universitas Islam Negeri Mataram, 2024)
The increasingly advanced development of industry impacts the development of transactions and production processes in an increasingly complex economy. Many transaction activities and production processes require ijtihad to find solutions to problems that may arise. The hope is that these transactions and production processes can run smoothly and follow Islamic law. This study aims to discuss how 'urf becomes a method and source of Islamic law in economic activities using a qualitative research methodology with a library research approach. This study concludes that Al-Urf in contemporary Islamic economic law provides a strong foundation through community customs that do not conflict with the Qur'an and Hadith. In responding to the challenges of the existing modern economy, it needs to be critically appreciated according to the context of its time, place, and situation, then developed according to the challenges of the times by using creative ijtihad in the corridor of sharia.